2015
DOI: 10.5539/gjhs.v8n8p114
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Hygiene Pattern and Behaviors and Related Factors among General Population in West Of Iran

Abstract: Introduction:Sleep hygiene was found as an important predictor for sleep quality. People’s sleep hygiene can have a major role in their daily function. The purpose of the study was to determine sleep hygiene patterns and sleep hygiene behaviors and factors affecting them in the general population of Kermanshah, Iran.Material and methods:In this cross-sectional study, 1829 men and 1262 women were selected randomly from 50 clusters of different parts of the city. The inclusion criteria were age between 12 and 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Also, sleep hygiene had no significant relationship with marital status, education, and occupation of older adults. Meanwhile, in a study by Khazaie et al who studied sleep hygiene patterns in Iranian adult population, sleep hygiene had a significant relationship with sex, age, occupation, and marital status of patients (20). This inconsistency can be due to the difference in the mean age of the two populations, that is, the population in their study was younger than ours (35 vs. 68.33) (20).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Also, sleep hygiene had no significant relationship with marital status, education, and occupation of older adults. Meanwhile, in a study by Khazaie et al who studied sleep hygiene patterns in Iranian adult population, sleep hygiene had a significant relationship with sex, age, occupation, and marital status of patients (20). This inconsistency can be due to the difference in the mean age of the two populations, that is, the population in their study was younger than ours (35 vs. 68.33) (20).…”
Section: Discussioncontrasting
confidence: 54%
“…Meanwhile, in a study by Khazaie et al who studied sleep hygiene patterns in Iranian adult population, sleep hygiene had a significant relationship with sex, age, occupation, and marital status of patients (20). This inconsistency can be due to the difference in the mean age of the two populations, that is, the population in their study was younger than ours (35 vs. 68.33) (20). Cho et al (21) reported a significant correlation between SHI and age.…”
Section: Discussionmentioning
confidence: 99%
“…The first two instruments have been found to have relatively low internal consistency compared to the SHI (Cronbach's alphas = 0.47 for the SHAPS, 0.54 for the SHST and 0.66 for the SHI). Moreover, SHAPS and SHST appear to have been developed with absence of clear rationale for item selection (11,16), while the SHI was developed from the diagnostic criteria for inadequate sleep hygiene as described in the ICSD (12,15). The SHI has shown moderate internal consistency and good twoweek test-retest stability (r = 0.71, P < .001), and was associated with sleep quality and daytime sleepiness in a nonclinical sample (11).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been increased attention to sleep quality and sleep hygiene. Sleep hygiene may be described as behavioral and environmental practices that promote sleep and avoiding behaviors that interfere with sleep (7, 11, 12). In the 2014-revised edition of the International Classification of Sleep Disorders (ICSD), inadequate sleep hygiene was classified as a subtype of chronic insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…The first two instruments have been found to have relatively low internal consistency compared to the SHI (Cronbach’s alphas = 0.47 for the SHAPS, 0.54 for the SHST and 0.66 for the SHI). Moreover, SHAPS and SHST appear to have been developed with absence of clear rationale for item selection (11, 16), while the SHI was developed from the diagnostic criteria for inadequate sleep hygiene as described in the ICSD (12, 15). The SHI has shown moderate internal consistency and good two-week test-retest stability (r = 0.71, P < .001), and was associated with sleep quality and daytime sleepiness in a nonclinical sample (11).…”
Section: Introductionmentioning
confidence: 99%